Ideal Test Time for Coronavirus Disease 2019 Contact Tracing - Miyake, Shigeta; Kato, Hideaki; Tanaka, Nobuko; Shimizu, Kohei; Ozawa, Hiroki; Kawakami, Chiharu; Usuku, Shuzo; Nakajima, Hideaki; Yamamoto, Tetsuya (Frontiers in Public Health, 2022)
Background Epidemiological contact tracing is a powerful tool to rapidly detect SARS-CoV-2 infection in persons with a close contact history with COVID-19-affected patients. However, it remains unclear whom and when should be PCR tested among the close contact subjects. Methods We retrospectively analyzed 817 close contact subjects, including 144 potentially SARS-CoV-2-infected persons. The patient characteristics and contact type, duration between the date of the close contact and specimen sampling, and PCR test results in PCR positive and negative persons were compared. Results We found that male gender {adjusted odds ratio 1.747 [95% confidence interval (CI) 1.180–2.608]}, age ≥ 60 [1.749 (95% CI 1.07–2.812)], and household contact [2.14 (95% CI 1.388–3.371)] are independent risk factors for close contact SARS-CoV-2 infection. Symptomatic subjects were predicted 6.179 (95% CI 3.985–9.61) times more likely to be infected compared to asymptomatic ones. We could observe PCR test positivity between days 1 and 17 after close contact. However, no subject could be found with a Ct-value <30, considered less infective, after day 14 of close contact. Conclusions Based on our results, we suggest that contact tracing should be performed on the high-risk subjects between days 3 and 13 after close contacts.